Analysis and design of a highly linear CMOS OTA for portable biomedical applications in 90 nm CMOS. (December 2017) - Elamien, Mohamed B.; Mahmoud, Soliman A.
Abstract: This paper presents the analysis and design of a new CMOS highly linear digitally programmable operational transconductance amplifier (DPOTA). The proposed DPOTA is used to design a fourth-order low pass filter for a portable Electroencephalogram (EEG), Electrocardiogram (ECG) and Electromyography (EMG) detection systems. The performance of the proposed DPOTA and the low pass filter is validated through simulation results using 90 nm CMOS technology under a balanced 1.2 V supply voltage. The transconductance value of the proposed DPOTA can be controlled, from 25 nA/V to 400 nA/V, by a 4-bit digital word. The IM3 of the proposed DPOTA is 45 dB with two single tones at frequency 60 Hz and 80 Hz and an amplitude of 20  m V p − p each. The low pass filter cutoff frequency can be adjusted to 107 Hz, 257 Hz, and 537 Hz. The third-order harmonic distortion (HD3) of the filter is 51 dB for 20  m V p − p at 100 Hz sinusoidal input signal.